75.5k views
23 votes
For which of the following decreasing functions ƒ does (ƒ-¹)'(10) = −1/8?

A) f(x)=-5x+15
B) f(x)=-2x^3-2x+14
C) f(x)=-x^5-4x+15
D) f(x)=e^(-2x)-x+9

User Jay Choo
by
5.0k points

1 Answer

5 votes

Recall the inverse function theorem; if
f(x) is locally invertible around
x = a, and
f(a) = b and
a = f^(-1)(b), then


f\left(f^(-1)(x)\right) = x \implies f'\left(f^(-1)(x)\right) \left(f^(-1)\right)'(x) = 1 \\\\ \implies \left(f^(-1)\right)'(x) = \frac1{f'\left(f^(-1)(x)\right)} \\\\ \implies \left(f^(-1)\right)'(b) = \frac1{f'(a)}

Then the given derivative value tells us that there is some value of
x=a for which
f(a)=10 and
f'(a) = -8. Compute the derivative of each function and check if both of these conditions are met.

  • If
    f(x)=-5x+15, then
    f'(x)=-5. (no)
  • If
    f(x)=-2x^3-2x+14, then
    f'(x)=-6x^2-2. Then
    f'(a) = -6a^2-2=-8 \implies a = \pm 1. Now,
    f(-1)=18 doesn't work, but
    f(1)=10 does. (B is the correct choice)
  • If
    f(x)=-x^5-4x+15, then
    f'(x)=-5x^4 - 4. Then
    f'(a)=-5a^4-4=-8 \implies a = \pm\sqrt[4]{\frac45}. But
    f(a)\\eq10 for either of these values. (no)
  • If
    f(x)=e^(-2x)-x+9, then
    f'(x)=-2e^(-2x)-1. Then
    f'(a)=-2e^(-2a)-1=-8 \implies a = \frac{\ln(2)-\ln(7)}2. But
    f(a)\\eq10. (no)
User KillianGDK
by
4.9k points